2018
DOI: 10.1002/mc.22819
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of fibroblast growth factor receptor 4 polymorphisms in primary breast cancer

Abstract: Fibroblast growth factor receptor 4 (FGFR4) belongs to the receptor tyrosine kinase (RTK) family, and FGFR4 polymorphisms have been implicated in both normal development and cancer, including breast cancer. In the present study, we investigated correlations between polymorphisms in FGFR4 and breast cancer prognosis. The FGFR4 SNPs rs1966265 and rs351855 were genotyped in 747 breast cancer patients using the SNaPshot method. FGFR4 protein expression was detected by immunohistochemistry in 339 samples. SNP rs351… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
6
14
0
Order By: Relevance
“…Furthermore, stratifying by type of cancer, we observed that this variant is correlated with prostate and breast cancer, but not with lung cancer. Our results are consistent with the studies conducted by Xu et al and Wei et al (Xu et al, 2011;Wei et al, 2018). In subgroup analysis by ethnicity, we also found that FGFR4 R-allele is correlated with an increased risk of cancer in Asian descendants.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, stratifying by type of cancer, we observed that this variant is correlated with prostate and breast cancer, but not with lung cancer. Our results are consistent with the studies conducted by Xu et al and Wei et al (Xu et al, 2011;Wei et al, 2018). In subgroup analysis by ethnicity, we also found that FGFR4 R-allele is correlated with an increased risk of cancer in Asian descendants.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that high levels of FGFR4 expression had a relationship with LNM in our previous study (Wei, You et al 2018). Consistent with these findings, our data revealed that high FGFR4 expression was correlated with LNM in TNBC patients.…”
Section: Discussionsupporting
confidence: 91%
“…The impact of FGFR4 on prognosis has been found in different cancers (Li, Zhang et al 2014, Huang, Feng et al 2015, Inokuchi, Murase et al 2017, and we also confirmed that patients with high FGFR4 expression had worse outcomes (Wei, You et al 2018). In the present study, TNBC patients with high FGFR4 expression tended to have shorter survival times than those with low FGFR4 expression ( Figure 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations